Model for Strengthening the Spiritual–Social Intelligence of Junior High School Students in Kuantan Singingi Regency - A Mualif; Amril Amril (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2026)
This study aims to analyze the influence of spiritual intelligence on students’ social intelligence and its implications for strengthening character education at the junior high school level. The background of this research is based on the importance of integrating spiritual and social dimensions in shaping students’ prosocial behavior, empathy, responsibility, and integrity amid moral challenges and rapid social change. This study employed a quantitative approach using a correlational survey design. The sample consisted of junior high school students selected through purposive sampling techniques. Data were collected using validated and reliable questionnaires measuring spiritual intelligence and social intelligence, and were analyzed using descriptive and inferential statistical methods. The findings indicate that spiritual intelligence has a positive and significant effect on students’ social intelligence. Higher levels of spiritual intelligence are associated with better interpersonal skills, empathy, and the ability to build harmonious social relationships. These results confirm that strengthening spiritual values within the educational process contributes significantly to the development of mature social character. This study recommends integrating spiritual intelligence development programs into the curriculum as a systematic strategy to support sustainable character education.